2019
DOI: 10.9767/bcrec.14.3.3472.568-578
|View full text |Cite
|
Sign up to set email alerts
|

CO2 Reforming of Methane over LaNiO3 Perovskite Supported Catalysts: Influence of Silica Support

Abstract: The study presents the dry reforming of methane using natural Kaolin silica as catalyst support. The silica-supported LaNiO3 perovskite catalysts (20LaNiO3/SiO2 and 40LaNiO3/SiO2) and bulk LaNiO3 catalyst were synthesized by auto-combustion method. The resulting catalysts were characterized by X-ray diffraction (XRD), N2 adsorption - desorption isotherm measurement,  scanning electron microscopy (SEM) and temperature-programmed reduction (TPR). After reduction at 700 °C, they were used as catalysts for the rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 32 publications
0
0
0
Order By: Relevance
“…This denotes the inability of silicate phase to encapsulate the nickel nanoparticles on the surface. Similarly, Sellam et al [63] investigated LaNiO 3 /SiO 2 -supported catalysts and reported an improved catalytic performance owing to the higher surface area and nanosized nickel particles. Zhang et al [142] prepared LaNiO3 perovskites supported on mesoporous silica and tried to capitalize the confinement effect derived from the use of this mesoporous material.…”
Section: Mesoporous/supported Perovskite Catalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…This denotes the inability of silicate phase to encapsulate the nickel nanoparticles on the surface. Similarly, Sellam et al [63] investigated LaNiO 3 /SiO 2 -supported catalysts and reported an improved catalytic performance owing to the higher surface area and nanosized nickel particles. Zhang et al [142] prepared LaNiO3 perovskites supported on mesoporous silica and tried to capitalize the confinement effect derived from the use of this mesoporous material.…”
Section: Mesoporous/supported Perovskite Catalystsmentioning
confidence: 99%
“…Several techniques by different scientific groups have been developed to transfuse higher carbon resistance and reduce carbon deposition [55,56]. For this purpose, materials with different structures, such as phyllosilicates [30,52,54,57], spinel [58][59][60], and perovskites [61][62][63][64][65], have been widely used as catalyst precursors.…”
Section: Brief Summary Of Ni-based Catalysts For Methane Dry Reformingmentioning
confidence: 99%